Peneparan Medote Transportasi Untuk Analisa Pengiriman Barang Pada JNT Aek Nabara - Suratika, Nadya; Manurung, Elisabeth Natasya; Harahap, Sri Handayani; Nasution, Iwan; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
This research analyzes goods delivery transportation methods at JNT Aek Nabara, North Sumatra, with a focus on cost efficiency and service quality. The three types of services analyzed are Sure Tomorrow Arrive (YES), Regular (REG), and OKE. The analysis methods used, including North West Corner (NWC), Least Cost, and Vogel's Approximation Method (VAM), show potential cost savings of up to 15%. Additionally, sensitivity analysis reveals that large changes in distribution parameters can affect overall delivery efficiency. This research concludes that choosing the right transportation method is very important to increase efficiency and recommends regular evaluation of distribution strategies based on real-time data to meet customer expectations.